Features of management of cardiac patients during the pandemic of coronavirus infection COVID-19 - Yu. N. Panina; V. I. Vishnevsky (Лечащий Врач, 2022)
Cardiac patients are at risk for a severe course of coronavirus infection, as treatments for COVID-19 may have side effects on the cardiovascular system. Also, patients with pre-existing cardiovascular diseases risk factors and cardiovascular diseases are among the most vulnerable, with a potentially high risk of infection, cardiovascular events, and adverse outcomes. COVID-19 is associated with many direct and indirect cardiovascular complications. In this regard, we analyzed a large amount of literature in the CochraneLibrary, ScienceDirect, PubMed databases, summarized modern scientific data and identified the features of the management of cardiac patients during the COVID-19 pandemic. It has been noted that careful monitoring of highly sensitive troponin I and troponin T can aid in the early detection of cardiac damage and possibly prevent further deterioration with appropriate treatment. Elevated troponin is indicative of myocardial injury, which can be caused by cytokine storm, hypoxic injury, coronary spasm, microthrombi, myocarditis, or plaque rupture. Systemic inflammation and hypoxemia caused by COVID-19 may also contribute to the development of various types of arrhythmias. In addition, severe inflammation can cause hemostasis disorders, including disseminated intravascular coagulation, microclot formation in the lungs, and intravascular coagulopathy. An increase in troponin levels may be secondary to, and not due to, plaque instability. At the same time, to date, the strategy for managing cardiac patients during a pandemic is not clearly defined and is mainly focused on supportive therapy, as well as on the treatment of the infection itself.